The Role of Children's Literature in the Training of Competitive Personnel - Ashurova Zulkhumor Shodiyevna (International Journal on Orange Technologies, 2021)
This article examines the role and place of children's literature in the years of independence in the training of qualified personnel. The analysis of the poem "The Genius Poet" by the children's poet O. Damin, dedicated to the work of A. Navoi, was carried out.